Study on the damping behaviour of eutectic high-entropy alloys with lamellar structures. (3rd June 2019) - Lin, Li-Feng; Tsai, Che-Wei
ABSTRACT: Damping is the ability to reduce the energy produced by vibrations in a system. In this research, the eutectic high-entropy alloys (EHEAs), AlCo x CrFeNi2.1 ( x = 0.7, 1.0 and 1.5), are firstly studied for their damping behaviour. EHEA is a promising concept of high-entropy alloys. By combining the advantages of eutectic phases and HEAs, the EHEAs show better liquidity, castability and compositional homogeneity than conventional HEAs. Meanwhile, it can strike a great balance in mechanical strength and tensile ductility owing to the lamellar structures. The microstructures and crystal structure of two near-EHEAs are also studied. AlCo0.7 CrFeNi2.1 is a hypo-eutectic HEA with primary body-centred cubic phases. AlCo1.5 CrFeNi2.1 is a hyper-eutectic HEA with primary face-centred cubic phases. The results showed that these eutectic and near-eutectic alloys gave rise to greater tan δ values than conventional dual-phase HEAs, which might be attributed to their lamellar structures.